1998
DOI: 10.1159/000023186
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Growth Hormone Replacement Therapy on IGF-Related Parameters and on the Pituitary-Gonadal Axis in GH-Deficient Males

Abstract: It has been suggested that growth hormone (GH) may play a regulatory role in male reproductive function. To express full anabolic effect in immature boys testosterone apparently requires the presence of GH. In GH-deficient adults, GH replacement therapy exerts a variety of anabolic actions, some of which are similar to the effects of gonadal steroids. However, little is known about the potential effects of GH on gonadal steroids and on dynamic tests of pituitary-gonadal function in adults with GH deficiency. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 34 publications
2
35
0
Order By: Relevance
“…There are no data to indicate that GH treatment increases PSA levels, in fact one study has shown the opposite [20]. The positive statistical correlation between circulating IGF-I and the development of prostatic cancer in normal males remains unexplained.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are no data to indicate that GH treatment increases PSA levels, in fact one study has shown the opposite [20]. The positive statistical correlation between circulating IGF-I and the development of prostatic cancer in normal males remains unexplained.…”
Section: Resultsmentioning
confidence: 99%
“…These effects, which were observed during a double-blind, placebo-controlled trial, were not associated with changes in circulating androgen levels. A study by Juul et al [20]involving GH treatment in a small group of young males with isolated GHD also failed to detect any changes in gonadotroph function (fig. 2), androgen levels and sperm quality.…”
Section: Sex Steroidsmentioning
confidence: 97%
See 1 more Smart Citation
“…GH has been shown to affect progesterone and estrogen synthesis [12]and testicular steroidogenesis [13, 14]by stimulation of several steroidogenic enzymes. On the other hand, GH treatment did not seem to affect gonadotropin or sex steroid patterns in normal subjects [15, 16]and did not influence the pituitary-gonadal axis in GHD patients [17]. …”
Section: Introductionmentioning
confidence: 99%
“…Reduced total sperm numbers have been reported in a group of patients with isolated GHD (4), whereas two other studies did not report any influence on spermatogenesis during GH replacement therapy (2,26). Experimental GH therapy has also been applied to infertile men without pituitary disease (27,28) or as adjuvant therapy during gonadotropin therapy of hypogonadotropic hypogonadism (29).…”
Section: Discussionmentioning
confidence: 99%